The Dynamics of Political Intolerance among Party Workers in Pakistan: An Empirical Study - Chohadry, Sarwat; Muzaffar, Muhammad (Annals of Human and Social Sciences, 2025)
This study was designed to examine the dynamics of political intolerance among party workers of Pakistan, recognizing the fat that historical and cultural roots of intolerance, the role of politics and religion in its growth have powerful impact on party workers in increasing political intolerance. This study is descriptive in nature and Quantative method by approach. The target population was the male and female political workers of four major political parties; Pakistan Muslim League Nawas, Pakistan People’s Party, Pakistan Tehreke Insaf and Tehreke labaik Pakistan. Political worker from federal capital Islamabad and provincial capitals; Gilgit Baltistan, (Gilgit) Sindh ,(Karachi), Punjab (Lahore ) Khyber Pakhtunkhwa (Peshawar) and Balochistan (Quetta) were taken as study sample by using cochran’s bach formula for taking sufficient sample size from the population. The data was collected with a questionnaire and was analyzed by applying descriptive and inferential statistic. The result of the study showed deep rooted historical, cultural, socio- economic causes plays a vital role in political intolerance of party workers of Pakistan and analysis of the questionnaire showed high condition of political intolerance in party workers of Pakistan. This study recommends that educational and political institution as well as public departments should promoting civic education, a trend of regard, inclusivity and democracy, political leaders avoid negative narratives and develop a negotiator environment then it is possible to reduce intolerant behaviour in part workers of Pakistan to make Pakistan a politically peaceful state. It also recommended that all parties should agree on a code of conduct that is respectful and free of violence, especially on social media and the media.